If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-5(x+5)=-3x-23
We move all terms to the left:
-5(x+5)-(-3x-23)=0
We multiply parentheses
-5x-(-3x-23)-25=0
We get rid of parentheses
-5x+3x+23-25=0
We add all the numbers together, and all the variables
-2x-2=0
We move all terms containing x to the left, all other terms to the right
-2x=2
x=2/-2
x=-1
| 8w+4=-9(w-8) | | 10/11=a+4/11 | | 3+b=28 | | 7(w-4)=-4w+38 | | -24-15y=-4 | | 91=13(-7x-42) | | -n-6=-8 | | 7-7x-4=-15+4x-15 | | 50x=7000+15x | | b^2+3b+b+3=0 | | 3x+7=12-2× | | 4x+1=7×-3 | | X-2y=37 | | 3+¼(x-4)=2/5(2+3x) | | -4=4(y+2)-8y | | 120=-4x+2(-3x+25) | | -34=4(v-7)+2v | | 5-(x-11)=6(x+10) | | 5(u+3)-2u=24 | | 2y-3/4=y-3/6 | | -3x+51=-36 | | 4-(x-11)=8(x+6) | | 2.9x=17.4 | | (6r+2)-(3r+5)=-18r+123 | | -16t^2+50t-36=0 | | 0.08k-0.2(k+5)=-0.1 | | .7x+.7=2.1 | | 4m^2+12m-72=0 | | 3y+2(-y-2)=-18 | | 5/(x+3)=0 | | -4{u-11}=-16 | | 164-23x=-27x-136 |